PENERAPAN NILAI-NILAI KEADILAN SOSIAL DALAM KONSTITUSI EKONOMI: Studi terhadap Pembatalan UU Sumber Daya Air oleh Mahkamah Konstitusi - Nanin Koeswidi Astuti (to-ra, 2020)
The state has a social responsibility towards citizens as stipulated in the constitution. Article 33 regulates economic management and Articles 23, 27, 28, 31, 34 regulate the social obligations of the state towards citizens. The state should manage the economy based on the articles in the constitution, or in other words, in the paradigm of an economic constitution, economic management by using national resources, both natural resources, human resources for the national interest in order to reduce economic inequality and create social welfare. The Constitutional Court decisions have been a form of commitment by the constitutional judges in carrying out the functions of the Constitutional Court as the guardian of the constitution, as one of the judicial power actors who have the authority to judge for the upholding of law and justice, that the SDA Law does not uphold the values ​​of social justice as regulated by the economic constitution. in the 1945 Constitution.